Therapeutic Potential of Ginger Ethanolic Extract, Ginger-Loaded Chitosan ‎Nanoparticles, and Chitosan Nanoparticles in Induced Type 2 Diabetes Mellitus in Dogss in Induced Type 2 Diabetes Mellitus in Dogs - M Hameed, Rasema; K Mahmood, Alaa (The Iraqi Journal of Veterinary Medicine, 2024)
Type 2 diabetes mellitus (T2DM) in dogs is a complex, multifactorial disease that is characterized by chronic hyperglycemia and insulin resistance. Current therapeutic options are often limited by side effects and variable efficacy, highlighting the need for more effective and safer treatments. This study assessed the therapeutic potential of ginger ethanolic extract (GEE), GEE-loaded chitosan nanoparticles (GEE-CNPs), and chitosan nanoparticles (CNPs) against T2DM in dogs. Twenty adult local breed mongrel dogs of both sexes, aged 7 to 13 months, with an average body weight of 10.4±0.76 kg, were included. The dogs were allocated into five groups (n=4 each): a non-diabetic, untreated Negative Control group, and four diabetic treatment groups, following T2DM induction via a single intravenous alloxan-nicotinamide injection. Each treatment group received daily oral administrations of either saline (Positive Control), GEE, GEE-CNPs, or CNPs at a dosage of 81.7 mg/kg BW over 45 days. Serum glycemic status (fasting serum glucose, insulin, and insulin resistance) was ‎recorded at baseline and on days 7, 14, 21, 28, 35, 42, and 45 post-treatments. ‎Additionally, on day 45, serum lipid profiles, liver function indicators (alanine aminotransferase [ALT], gamma-glutamyl transferase [GGT], and bilirubin), and ‎markers of antioxidant status (glutathione [GSH] and malondialdehyde [MDA]) were assessed.‎ The results showed that dogs in the diabetic Positive Control group ‎exhibited ‎hyperglycemia, dyslipidemia‎, liver ‎dysfunction, and elevated ‎oxidative stress markers, ‎‎underscoring the severe impact of T2DM. Compared to the diabetic Positive Control, oral GEE, GEE-CNPs, and CNPs ‎treatments significantly (P<0.05) improved ‎fasting glucose levels, insulin sensitivity, lipid profiles (reduced total cholesterol, ‎triglycerides, and LDL-C), liver function markers, and antioxidant status, indicating ‎enhanced metabolic health and reduced oxidative stress. The findings suggest that GEE, GEE-CNPs, and CNPs offer potential as therapeutic agents for T2DM in dogs, demonstrating ‎significant benefits in glycemic control, lipid normalization, liver function, and oxidative ‎stress reduction. Further investigations with larger cohorts and longer durations are ‎recommended to confirm these results and ascertain the clinical applicability and safety of ‎these natural remedies in managing canine diabetes‎‎‎.